Occurrence of pathogenic microorganisms in small drinking-water systems in Costa Rica. (3rd February 2022) - Barrantes, Kenia; Chacón, Luz; Morales, Eric; Rivera-Montero, Luis; Pino, Macario; Jiménez, Alejandra Gamboa; Mora, Diana Campos; Jiménez, Pablo Salas; Silva, Basilio; Romero-Esquivel, Luis G.
Abstract: This study describes the quality of drinking water sampled over 2 years (2018 and 2019) from 20 ASADAS (Spanish acronym for Administrative Associations for Water and Sewer Systems ) in Costa Rica. The analysis included Rotavirus (RV), somatic coliphages, fecal coliforms, and Escherichia coli . The ASADAS were categorized into three regions as temperate rainy (region 1), tropical rainy (region 2), and tropical rainy and dry (region 3) according to biogeographic classification. The concentrations of fecal coliforms and E. coli were higher in samples from surface water sources from the ASADAS in region 3 compared to regions 1 and 2. RV-positive samples (24/296) were detected in drinking-water samples from regions 2 and 3 during dry and transition seasons, with higher concentrations more frequently in the dry season. In addition, somatic coliphages were detected in samples from the three regions, with higher concentrations in region 2. Furthermore, a statistically significant relationship was found between somatic coliphages and diarrheal cases, classified as outbreaks or alerts in the region. Thus, the results confirmed that somatic coliphages are a good indicator of the presence of diarrhea cases in a specific region. HIGHLIGHTS: Rotaviruses (RVs) are frequent waterborne pathogens. Fecal coliforms, Escherichia coli, somatic coliphages, and RV were analyzed from drinking-water samples in Costa Rica. A significant relationship was found between somatic coliphages and diarrheal cases. Somatic coliphages are considered a good indicator of diarrhea-causing pathogens in a specific region.